Implementation Of Islamic Music Therapy Intervention (Sholawat Asqil) on Mental Disorder Clients With Hearing Hallucinations in the Melati Room RSJ. Dr Radjiman Wediodiningrat - Latif, Fauzan Abdul; J.A.H, Ns. Maulidiyah; Fauzi, Ahmad Kholid (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Hallucinations are one of the symptoms of sensory perception disorders experienced by patients with mental disorders, usually sufferers feel the sensation of sound, sight, taste, touch, or smell without any real stimulus. Approximately 70% of hallucinations experienced by patients with mental disorders are auditory hallucinations. One of the therapies that can be used to treat auditory hallucination patients. Purpose: This study aims to identify the application of Islamic music therapy interventions to mentally ill patients with auditory hallucinations in the Melati Room of RSJ Dr. Radjiman Wediodiningrat. Methods: Data collection techniques using interviews, observation, physical examination and documentation, implementation of Islamic music therapy to control auditory hallucinations. Results: Data analysis showed that the nursing diagnosis was sensory perception disorder. Providing Islamic music therapy is one of the interventions that can be applied to control hallucinations. Conclusion: Based on the evaluation results obtained from nursing care, Islamic music therapy can control auditory hallucinations